2011
DOI: 10.1016/j.foreco.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Response of bat species to sylvo-pastoral abandonment

Abstract: a b s t r a c tWe assessed the effect of abandonment of sylvo-pastoral practices in chestnut orchards (Castanea sativa) on bats in southern Switzerland to determine practical recommendations for bat conservation. We compared bat species richness and foraging activities between traditionally managed and unmanaged chestnut orchards, testing the hypothesis that managed orchards provide better foraging opportunities and harbour more bat species. Echolocation calls of foraging bats were sampled simultaneously at pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 63 publications
3
28
0
Order By: Relevance
“…Moreover, Obrist et al (2011) showed experimentally that foliage density only weakly (≈5%) 334 attenuates calls at frequencies between 20-60 kHz, and the bat species we studied are not known to 335 change call frequency substantially in relation to the habitat they preferably use. Of more concern is 336 the likelihood that bats may reduce call intensity when flying in dense vegetation, making them less 337 likely to be detected.…”
Section: Temperature 300mentioning
confidence: 83%
“…Moreover, Obrist et al (2011) showed experimentally that foliage density only weakly (≈5%) 334 attenuates calls at frequencies between 20-60 kHz, and the bat species we studied are not known to 335 change call frequency substantially in relation to the habitat they preferably use. Of more concern is 336 the likelihood that bats may reduce call intensity when flying in dense vegetation, making them less 337 likely to be detected.…”
Section: Temperature 300mentioning
confidence: 83%
“…[54,55] for fungus species diversity). Forest management and the creation of novel forest habitats such as parks do not always have a negative effect on forest biodiversity, as the optimization of stand structure can result in SFP that support a high diversity of vascular plants [56,57], insects [58,59] and bats [60,61]. The positive effect of management on biodiversity, however, is generally driven by the increase of habitat generalists or open habitat species [43,62].…”
Section: In Situ Services Biodiversitymentioning
confidence: 99%
“…Abandoned groves quickly become invaded by other tree species and disappear entirely within decades as they evolve into dense mixed forests (Conedera et al 2000). In a parallel study we found twice the number of bat species (12) and 5 times higher total foraging activity in managed chestnut orchards compared to unmanaged ones, this effect being particularly pronounced in bat species with low flight manoeuvrability (Obrist et al 2011). Large mature chestnut trees very often have rotten trunks and branches, offering an exceptional variety of cavities (Spada et al 2008) for many treedwelling species (Moretti et al 2003(Moretti et al , 2004.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 53%
“…We suggest that this pattern is triggered by social factors related to the mating behaviour of the species that can be primarily explained by flight constraints. With their long, narrow wings (relatively small wing area and high wing loading), Leisler's bats are among the fastest-flying bats (Obrist et al 2011), a trait possibly crucial for long-distance migration and foraging, which however dramatically reduces flight manoeuvrability. During the courtship season, constraints in manoeuvrability might prove a limitation when Leisler's bat males engage in display flights to attract mates to their roosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation